A socio-ecological systems approach to understanding development in a dynamic world : a case study of traditional agriculture in Pondoland, South Africa - Kennedy, Kristen (Department of Environmental and Geographical Science, 2015)
Arguably one of the greatest challenges currently facing humankind is the linking of environmental sustainability with poverty reduction and social justice. These issues all come to a head in the rural smallholder agricultural regions of "underdeveloped" Africa .In these settings climate change and food security are but two of the many challenges faced on a daily basis, compounded by the need for "development". Through a case study of smallholder farmers facing multiple contested development trajectories, this research takes a social-ecological systems approach in order to: 1. investigate the past, present and future dynamics of smallholder agriculture and food practices in mPondo communities of the Wild Coast 2. locate the role of agriculture and agri-food systems in the local development discourses 3. describe the perceived opportunities and challenges which face the local agri-food system Through semi-structured interviews, informal discussions, workshops and participant observation in three regions of the Wild Coast of the Eastern Cape a trend of rapid cultural erosion was observed. Many traditional crops are no longer cultivated as farmers turn to commercial seeds and modern cooking methods. Three dominant development trajectories are explored for one region, focusing on the AmaDiba community whose history of resisting imposed development is again being tested by contentious titanium mining proposed in nearby Xolobeni. A central finding is that while resisting imposed development in order to achieve a self-defined development which values mPondo traditions and subsistence off the land, these communities - described as possessing strong community agency - are losing the very culture they are fighting to defend. This is made clear through the social-ecological systems approach of resilience theory. In building resilience to imposed development the community has become vulnerable to other disturbances. As this traditional agri-food system continues to face the enduring shocks of global environmental and social change, the communities must recognise their fragilities as well as the threats which have been overlooked in the past. This study therefore suggests that the community exploit this stage of readjustment so as to reorganise, building on local culture and tradition, through an integrated approach to development which combines agriculture, traditional food and tourism.